POSISI DAYA SAING PRODUK DAN KELEMBAGAAN AGROINDUSTRI HALAL ASEAN - Dwi Purnomo; E.Gumbira- Sa’id; Anas M Fauzi (JURNAL TEKNIK INDUSTRI, 2012)
Indonesia is the largest Muslim population in the world. By establishing Halal-based agro-industry, Indonesia is expected to avoid the status of the largest world’s largest Halal market. Indonesia need to gradually develop its capability as internationally recognized competitive Halal products producer. Malaysia, Thailand and Brunei Darussalam as ASEAN members have been globally recognized as the world’s Halal products hub and building their Halal industry as their main platform of agro-industry development to penetrate international market. High level of competition abounds from both Muslim and non-Muslim nations, including ASEAN members which have been aggressively setting up their industrial estates and marketing their Halal products around the global market. This study observed Halal-based Agro-industry Competitiveness among six ASEAN countries. Quantitative SWOT analysis and Multi Criteria Decision Making (MCDM) analysis were used to find out the details of intrinsic and extrinsic factors in each country. The result showed that Malaysia and Thailand placed as the most advance country among ASEAN countries, while Indonesia placed as number five due to its weakness in some most important intrinsic and extrinsic factors